Oxidation of triethylene glycol and tetraethylene glycol by ditelluratocuprate(III) in alkaline medium - A kinetic and mechanistic study - Shan, Jinhuan; Li, Yi (European Journal of Chemistry, 2013)
The kinetics of oxidation of triethylene glycol (TEG) and tetraethylene glycol (TTEG) by ditelluratocuprate(III) (DTC) in alkaline liquids were investigated spectrophotometrically in the temperature range of 20oC to 40oC. It was found that the reaction followed pseudo-first order in DTC and less than unit order in reductants. The rate constant kobs of pseudo-first order reaction decreased with an increase of [TeO42-], whereas adding [OH-] enhanced the constant. In addition, there was a negative salt effect. A suitable assumption involving pre-equilibriums before the rate controlling step and a free radical mechanism was proposed from the kinetics study. The rate equations derived from mechanism can explain all experimental phenomena. Moreover, the activation parameters at 298.2K and rate constants of the rate-determining step were evaluated.